QoS-Based Optimization of Runtime Management of Sensing Cloud Applications - Gotin, Manuel (The Karlsruhe Series on Software Design and Quality, 2022)
IoT applications perceive and interact with the environment via smart devices and cloud services. When operating such applications one is faced with the challenge of configuring the smart devices and the cloud services in a manner, which achieves a high data quality at low operational costs. This work supports IoT operators with IoT collection strategies and cost optimization functions for data qualities, which are influenced by the interplay of smart device and cloud service configurations.